CH3 photo-fragmentation laser-induced fluorescence for turbulent flame diagnosis - Carter, Campbell D.; McGann, Brendan J.; Eckhart, Stephen D.; Nilsson, Sebastian (Combustion and Flame, 2025)
We describe development and application of the CH3 photo-fragmentation laser-induced fluorescence (PF-LIF) diagnostic whereby CH is created and then detected. Specifically, we employed sum-frequency generation to produce 5th-harmonic output from a Nd:YAG laser (λ = 212.8 nm) for photolyzing CH3. The residual 2nd-harmonic beam was then used to pump a dye laser, the output of which was frequency-doubled and tuned to excite CH R-branch transitions within the C−X (0,0) band (λ ≈ 311 nm). We detected the resulting fluorescence from the C−X band, suppressing laser scattering using a custom long-wave-pass filter. Noteworthy features of the diagnostic are the inclusion of i) a diffractive-optical element (DE) in the 213-nm beam path, which imposes a spatial pattern on the photolysis product CH and thus a pattern on the images of CH planar laser-induced fluorescence, and ii) a laser-sheet monitoring system. We also demonstrated the simultaneous acquisition of CH3 images (via CH3 PF-LIF) and OH images by tuning to overlapped CH C−X (0,0) and OH A−X (0,0) lines. The CH3 distribution is thus distinguishable from that for OH by the spatial pattern generated by the DE, and an additional noteworthy feature of the diagnostic is development of a machine-learning algorithm for automated separation of the CH3 and OH signals. We conducted proof-of-concept measurements in a laminar premixed flame and a lifted jet diffusion flame and then validation measurements in the PRECCINSTA model gas-turbine burner. These validation measurements show that the flamefront bordering the inner recirculation zone (IRZ) was generally anchored to the burner's central cone; the same is not true of the flame bordering the outer recirculation zone (ORZ), where the flame was weakly burning and apparently influenced by the fluctuating quantity of OH and other combustion products within the ORZ.
Keywords: CH detection; Combined OH/CH imaging; Flamefront imaging; Turbulent combustion